ROLE OF VIRUDDHA AHARA AS A CAUSATIVE FACTOR OF KUSTHA ROGA W.S.R. TO VIRYA VIRUDDHA - A REVIEW AND ANALYTICAL STUDY - Pallavi Das*,; Khagen Basumatary, (AYUSHDHARA, 2018)
In Ayurveda the concept of Viuddha ahara has been condensed. It is one of the potent causative factors for several diseases. Consumption of Virddha ahara gives rise to various disturbances of mild to severe nature and disease of acute to chronic nature including the eight Maharogas, genetic disturbances and even sometimes causes death of the person. In Ayurveda skin disease is given importance and its given in different ancient classics of Ayurveda. The knowledge about skin and skin disorders are beautifully described in Ayurvedic literatures since Vedic period. In skin diseases, Viruddha ahara is considered as one of the prime factor for causing the disease and amongst all the Viruddha ahara, Virya viruddha is considered as the main cause. When substances having opposite Viryas are used in combination, that is known as Virya viruddha Kustha roga like Kotha, Utkotha, Shitapitta all these comes under allergic skin disorders. In this study, evaluation of the role of Viruddha ahara in Kustha Roga with emphasis on Virya Viruddha.